2009
DOI: 10.1021/jf901083d
|View full text |Cite
|
Sign up to set email alerts
|

Stability Studies on Astaxanthin Extracted from Fermented Shrimp Byproducts

Abstract: To the best of our knowledge, stability studies on astaxanthin contained in carotenoproteins extracted from lactic acid fermented shrimp byproduct have never been reported. Carotenoprotein powder, containing 1% free astaxanthin, was subjected to oxidation factors of illumination, oxygen availability, and temperature, using synthetic astaxanthin as a control. The individual effects as well as first and second degree interactions were studied on natural and synthetic free astaxanthin stability. Air and full ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 21 publications
2
30
0
3
Order By: Relevance
“…air' at 30°C (35.27-40.53 % degradation) had the highest astaxanthin degradation after 40 days of storage (p \ 0.05). The result was in accordance with Armenta and Guerrero-Legarreta (2009) who reported that the combination of full light, oxygen (air) and high temperature (45°C) caused the pronounced oxidation of astaxanthin. This result indicated that the combination of light, air and high temperature should be avoided during storage.…”
Section: Changes In Astaxanthin In Shrimp Oilsupporting
confidence: 92%
See 1 more Smart Citation
“…air' at 30°C (35.27-40.53 % degradation) had the highest astaxanthin degradation after 40 days of storage (p \ 0.05). The result was in accordance with Armenta and Guerrero-Legarreta (2009) who reported that the combination of full light, oxygen (air) and high temperature (45°C) caused the pronounced oxidation of astaxanthin. This result indicated that the combination of light, air and high temperature should be avoided during storage.…”
Section: Changes In Astaxanthin In Shrimp Oilsupporting
confidence: 92%
“…Comparison of means was carried out by Duncan's multiple range test at a significant level (p \ 0.05). For the design with interactions, a complete factorial experimental design was applied (Armenta and Guerrero-Legarreta 2009). Statistical analysis was performed using the Statistical Package for Social Science (SPSS for windows, SPSS Inc., Chicago, IL, USA).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of light is important to preserve the chemical stability of astaxanthin as this pigment is sensitive to light (Christophersen, Bertelsen, Andersen, Knuthsen, & Skibsted, 1992). When astaxanthin extracted from fermented shrimp byproduct was stored under darkness, reduced light and full light after 8 weeks, the astaxanthin oxidation was 1, 23, and 35% (Armenta & Guerrero-Legarreta, 2009). Our study showed a similar result that the astaxanthin extract from H. pluvialis was sensitive to light, and they should be stored under darkness to protect their oxidation activity.…”
Section: Antioxidative Stability Of Astaxanthin Extract From Supercrimentioning
confidence: 99%
“…These can cause discoloration and reduce the nutritional value and beneficial health properties of food containing carotenoids (Li et al, 2013). Astaxanthin (3, is the predominant carotenoid present in shrimps (fillet and shells), lobsters, fishes (trout and salmon) and some microorganisms (Suh;Joo;Lee, 2006;Niamnuy;Devahastin;Soponronnarist, 2008b;Nguyen, 2013), with a red-orange color (Miao et al, 2006;Kusdiyantini et al, 1998;Armenta;Guerrero-Legarreta, 2009). It removes the singlet oxygen ( 1 O 2 ) and the peroxyl radicals (H 2 O 2 ) from the medium in a more efficient way than do β-carotene (10 times more), canthaxanthin and zeaxanthin (Palozza;Krinsky, 1992), and exceeds (500 times more) the antioxidant effect (Higuera-Ciapara; Félix-Valenzuela; Goycoolea, 2006;Hussein et al, 2006b) of vitamins C and E (Palozza;Krinsky, 1992;Suh;Joo;Lee, 2006).…”
Section: Introductionmentioning
confidence: 99%